State Responses to the Opioid Crisis. Issue 2 (2018) - Parker, Andrew M.; Strunk, Daniel; Fiellin, David A.
Abstract : This paper focuses on the most common state policy responses to the opioid crisis, dividing them into six broad categories. Within each category we highlight the rationale behind the group of policies within it, discuss the details and support for individual policies, and explore the research base behind them. The objective is to better understand the most prevalent state responses to the opioid crisis.